End-to-End Deep Learning and Machine Learning Framework for Chronic Heart Failure Detection from Phonocardiogram Signals. - Lavanya , Komati; Naveen , Kanne; Nowsheen , Gazala; Vandana, Palle; Rudrarapu, Rajakumar (Journal of Neonatal Surgery, 2025)
Heart failure (HF), characterized by the heart's inability to effectively pump blood, is a chronic and progressive disease that may lead to death. Early and accurate diagnosis is crucial for optimal patient care and disease management. Though reliable, conventional diagnosis methods such as echocardiogram are costly, require specialized equipment, and are not typically accessible in resource-poor settings. Phonocardiogram (PCG) signals are acquired through non-invasive, affordable digital stethoscopes and thus serve as a promising candidate for automated screening of cardiac diseases. To identify CHF from PCG signals, in this work, a hybrid model based on E2E DL and traditional ML is proposed. Specifically, the method applies robust preprocessing, then segments the cardiac cycle, and extracts discriminative time-frequency features such as spectrograms and Mel-frequency cepstral coefficients (MFCCs). We also compare the end-to-end CNN architectures, which are directly learned from spectrogram representations, with traditional machine learning classifiers, including Random Forests and Support Vector Machines (SVM) with similar features extracted from spectrograms. The proposed CNN-based method outperforms traditional ML algorithms with an accuracy greater than 96%, sensitivity of 95.4%, and specificity of 96. 7% based on extensive evaluation using publicly available and carefully curated CHF-PCG datasets. The results show the potential of deep learning-based heart sound analysis for high performance, low-cost, and widely accessible CHF screening in hospitals and home-based healthcare.